War Against Inflation : The story of the falling rupee, 1943-77 - Vakil, C. N. (Delhi : Macmillan, 1978)
The object of the book is to explain how inflation has come in the way of progress and the removal of poverty and emphasise how the maintenance of comparatively stable price level in the context of priority for wage-goods in the planning process, will go a long way in solving the chronic problems of poverty and unemployment.
Includes bibliographical references and index.
osc 08/06/17
Loans
Keywords: Inflation (Finance); Fiscal policy; Monetary policy